Synchronization of Fibroblasts Ex Vivo in Psychopharmacology - Faltraco, Frank; Uzoni, Adriana; Shevchuk, Liliia; Thome, Johannes; Palm, Denise (Pharmacopsychiatry, 2020)
The central oscillator for the inner clock is the suprachiasmatic nuclei of the hypothalamus. Furthermore, many peripheral oscillators are present in tissues such as skin. Human derived fibroblasts provide an advantageous model to study circadian rhythmicity as well as the influence of pharmacological drugs on circadian gene expression. Importantly, the synchronization of the circadian system of fibroblasts can be done by different methods. The review presents an overview of the current knowledge of different synchronization methods mostly used in mice or rat fibroblasts. Furthermore, the review sums up and discusses the role of norepinephrine as a possible synchronizer agent.
Keywords: fibroblasts; circadian rhythm; synchronization